The out-of-school possibilities of language acquisition are important for adult learners - Kazi Balázs (2004)
This thesis examines the possibilities of acquiring language outside the school. I will prove the importance of this field. Using the results of my questionnaire and student feedback with background literature I will demonstrate that this mainly uncharted territory is a vital part of language learning. Both teacher and learner should consider the possibilities lying in the subject. This thesis also contains a systematic synopsis of ways of practicing the skills for learners willing to spend time on preserving their proficiency in English.